Promotional Strategies on Social Media for SMP Bina Taruna in Increasing Awareness: Strategi Promosi pada Media Sosial SMP Bina Taruna dalam Meningkatkan Awareness - Aisyi Syafikarani; Rahmiati Aulia; Olivine Alifaprilina Supriadi; Rully Sumarlin; Aria Ar Razi; Adya Mulya Prajana (Universitas Lancang Kuning, 2023)
SMP Bina Taruna only has social media on Instagram with the account name smp_binataruna.official. The account has 288 followers and 67 following. Apart from that, the number of posts uploaded is still small, only 19 feed posts have been posted since March 24th. In addition, when viewed from a visual perspective, it still does not represent the image of SMP Bina Taruna. There is still no graphic that unites every visual that is created. Visual assets in the form of photos or videos that are made also do not represent the message to be conveyed. Therefore, an integrated promotion strategy is needed, which can later be implemented in several adequate promotional media. As well as being able to increase awareness of SMP Bina Taruna